The Role of Work Environment in Moderating the Influence of Leadership on Work Motivation at BAZNAS Garut Regency - Mulyawan, Bintang Azrieel; Oktaroza, Magnaz Lestira; Purnamasari, Imas (Journal Corner of Education, Linguistics, and Literature, 2025)
This study aims to examine the impact of leadership on employee work motivation and to investigate the role of the work environment as a moderating variable in this relationship. A quantitative approach with a descriptive correlational design was employed for this research. Data were collected through a questionnaire administered to 50 BAZNAS Garut District staff members selected via total sampling. Data analysis was conducted using moderation regression with the assistance of statistical software. The findings indicate that leadership has a positive and significant effect on work motivation. Furthermore, the work environment has been shown to enhance the relationship between leadership and work motivation. The implications of these findings highlight the importance of developing effective leadership styles and creating a conducive work environment to boost employee morale in the Islamic philanthropy sector.